2019
DOI: 10.1007/s13272-019-00383-4
|View full text |Cite
|
Sign up to set email alerts
|

A review of acoustic imaging methods using phased microphone arrays

Abstract: Phased microphone arrays have become a well-established tool for performing aeroacoustic measurements in wind tunnels (both open-jet and closed-section), flying aircraft, and engine test beds. This paper provides a review of the most wellknown and state-of-the-art acoustic imaging methods and recommendations on when to use them. Several exemplary results showing the performance of most methods in aeroacoustic applications are included. This manuscript provides a general introduction to aeroacoustic measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(121 citation statements)
references
References 167 publications
(343 reference statements)
0
121
0
Order By: Relevance
“…The resulting microphone auto spectra and cross spectra were then averaged to obtain the final cross spectral matrix. In order to separate the different noise sources, a variety of advanced beamforming algorithms are available especially for aeroacoustic measurements [23]. It was finally decided to use the CLEAN-SC deconvolution beamforming algorithm [24], which was applied to the cross spectral matrizes.…”
Section: Microphone Array and Data Processingmentioning
confidence: 99%
“…The resulting microphone auto spectra and cross spectra were then averaged to obtain the final cross spectral matrix. In order to separate the different noise sources, a variety of advanced beamforming algorithms are available especially for aeroacoustic measurements [23]. It was finally decided to use the CLEAN-SC deconvolution beamforming algorithm [24], which was applied to the cross spectral matrizes.…”
Section: Microphone Array and Data Processingmentioning
confidence: 99%
“…Functional beamforming [59,60] was selected in this case, as it provides better dynamic range and array spatial resolution than CFDBF, and these features are very important for flyover measurements, due to the relatively large distance between source and observer [24,26,36]. Comparative studies with other acoustic imaging methods showed that functional beamforming [24,38] provides better results when applied to flyover measurements.…”
Section: Iiib Methods For the Flyover Measurementsmentioning
confidence: 99%
“…For aeroacoustic measurements, it is common to employ phased microphone arrays and acoustic imaging techniques for estimating the locations and strengths of the sound sources [8,[35][36][37][38] and isolate their contributions. These devices require short measurement times, allowing for relatively cheap and fast experiments [39].…”
mentioning
confidence: 99%
“…More advanced beamforming techniques applied to fullscale jet noise measurements have provided increased capabilities to characterize the acoustic source properties. The aeroacoustics community has developed improved beamforming methods that share many similarities with identification methods 6 -such as near-field acoustical holography (NAH) 23 and Helmholtz equation least squares (HELS) 24 -to solve for acoustic sources as a system instead of independently. 5 Dougherty and Mendoza 11 applied near-field beamforming and deconvolution techniques [i.e., the deconvolution approach for the mapping of acoustic sources (DAMAS) 25 and CLEAN for spatial source coherence (CLEAN-SC) 26 ] to engine and jet noise beamforming results using measurements from a 100-ft-radius polar arc array near a Honeywell Tech977 engine.…”
Section: B Advanced Beamforming In Jet Noisementioning
confidence: 99%
“…4 Phased-array techniques, e.g., beamforming, instead rely on the acoustic radiation to estimate the corresponding sources and thereby complement flowfield investigations. Standard beamforming can localize the jet noise sources, while more generalized methods-which have ties to both beamforming and source identification methods 5,6 -can estimate both the levels and coherence properties of the resulting source distributions. Application of generalized beamforming methods require additional considerations due to the directive, extended, and partially correlated sources of the jet noise.…”
Section: Introductionmentioning
confidence: 99%